Optimal Value and Post Optimal Solution in a Transportation Problem (Journal of Nonlinear Modeling and Analysis, 2024)
In this work, we analyse the transportation problem of a real-lifesituation by obtaining the optimal feasible solutions, thus carrying out thesensitivity analysis of the problem. The work utilises the data obtained fromthe Asejire and Ikeja plants of Coca-Cola company, aiming to aid decision-making regarding the best possible options to satisfy customers at the barestminimum cost of transportation. Rerunning the optimization of a problem isan expensive scheme for gathering and obtaining enough data required for aproblem. Thus, to minimize the transportation cost, the sensitivity analysis ofparameters is a good tool to determine the behaviour of some input parameterswhere the values of these parameters are varied arbitrarily such that optimalresults are verified. Maple 18 Software is used to solve the problem and theresult obtained is compared with the values evaluated from northwest cornermethod, least cost method and Vogel’s approximation method. The studycritically shows how a little change in a unit or more of any model parameteraffects the expected results.
Keywords: Optimal solution; Sensitivity analysis; Transportation.